2015
DOI: 10.11138/jpm/2015.9.1.012
|View full text |Cite
|
Sign up to set email alerts
|

A comparison between amniotic fluid index and the single deepest vertical pocket technique in predicting adverse outcome in prolonged pregnancy

Abstract: oligohydramnios is more frequently diagnosed using AFI than SDVP, consequently determining a higher rate of induction of labor. Moreover, perinatal outcome in prolonged induced pregnancies is not affected by oligohydramnios.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 25 publications
2
19
0
Order By: Relevance
“…Odds of experiencing composite adverse maternal outcome nearly doubles, triples and quadraples in women with hypertensive disorders of pregnancy compored to those whithout, oligohydramnios at early term gestation compared to those at full term and in those who are not married compared with those who are married respecrtively but these variables did not show an actual signi cant stastistical trend [ Table 8]. The rate of oligohydramnios [2.6%] in the present study is in agreement with other studies done in Ethiopia, India, Nigeria, Israel and USA which reported similar rates [1,7,36,37].…”
Section: Sample Size Determinationsupporting
confidence: 89%
See 1 more Smart Citation
“…Odds of experiencing composite adverse maternal outcome nearly doubles, triples and quadraples in women with hypertensive disorders of pregnancy compored to those whithout, oligohydramnios at early term gestation compared to those at full term and in those who are not married compared with those who are married respecrtively but these variables did not show an actual signi cant stastistical trend [ Table 8]. The rate of oligohydramnios [2.6%] in the present study is in agreement with other studies done in Ethiopia, India, Nigeria, Israel and USA which reported similar rates [1,7,36,37].…”
Section: Sample Size Determinationsupporting
confidence: 89%
“…Different tests have been proposed to determine amniotic uid volume as mean of evaluation of fetal wellbeing [12]. Amniotic uid index [AFI] and single deepest pocket [SDP] are the most-used semiquantitative techniques.…”
Section: Methods Of Determining Amniotic Uid Volumementioning
confidence: 99%
“…6 Obstetricians plan delivery by induction of labor or caesarean section after diagnosis of decreased amniotic fluid volume at term, to prevent an adverse pregnancy outcome. 7 The method of amniotic fluid volume estimation using the amniotic fluid index increased the number patients who were diagnosed with oligohydramnios and polyhydramnios which in turn leads to an abnormal fluid volume when compared with the single largest pocket measure. In a study by Alfirevic 8 et al 490 patients where considered showed that a significantly greater number of patients were considered to have oligohydramonos when amniotic fluid index was used than with single largest pocket.…”
Section: Discussionmentioning
confidence: 99%
“…Despite considerable doubts regarding the best noninvasive method of estimating amniotic fluid volume and its effectiveness in predicting perinatal outcomes, the AFI is still preferred in routine clinical practice . Furthermore, the relationship between borderline AFI and perinatal outcomes was widely studied, also remains controversial.…”
Section: Discussionmentioning
confidence: 99%